2010
DOI: 10.1111/j.1365-2052.2009.01993.x
|View full text |Cite
|
Sign up to set email alerts
|

High mitochondrial differentiation levels between wild and domestic Bactrian camels: a basis for rapid detection of maternal hybridization

Abstract: Hybridization between wild species and their domestic congeners often threatens the gene pool of the wild species. The last wild Bactrian camel (Camelus ferus) populations in Mongolia and China are examples of populations facing such a hybridization threat. To address this key issue in the conservation of wild camels, we analysed wild, hybrid and domestic Bactrian camels (Camelus bactrianus) originating from Mongolia, China and Austria. Through screening of an 804-base-pair mitochondrial fragment, we identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 26 publications
1
44
1
Order By: Relevance
“…All studies found that the genetic variation within breeds was much greater than the genetic variation between the breeds. Our results were not consistent with the results of Silbermayr et al (2010), who found in their study both wild and domesticated camels that most genetic variation between and within the breeds was 95.64% and 4.36% respectively. Ming et al (2016b) also found that between breed variance was 90.14% and within breed was 9.86% in their studies of wild and domesticated camels.…”
Section: Analysis Of Molecular Variance (Amova)contrasting
confidence: 57%
See 1 more Smart Citation
“…All studies found that the genetic variation within breeds was much greater than the genetic variation between the breeds. Our results were not consistent with the results of Silbermayr et al (2010), who found in their study both wild and domesticated camels that most genetic variation between and within the breeds was 95.64% and 4.36% respectively. Ming et al (2016b) also found that between breed variance was 90.14% and within breed was 9.86% in their studies of wild and domesticated camels.…”
Section: Analysis Of Molecular Variance (Amova)contrasting
confidence: 57%
“…Ming et al (2016b) also found that between breed variance was 90.14% and within breed was 9.86% in their studies of wild and domesticated camels. Evolution of domesticated and wild camels was in the form of two distinct chains might be the reason behind these finding, and it is suggested that they do not have the same origins (Silbermayr et al, 2010) demoGraphic expanSion (Table 2).…”
Section: Analysis Of Molecular Variance (Amova)mentioning
confidence: 99%
“…2010a) and nine new ones (GenBank submission KF640722–KF640727 and KF640729–KF640731). Molecular diversity indices over all Mongolian Bactrian camels are detailed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…2010a) on the MegaBACE 1000. The amplicons were aligned to a reference genome (NC_009628.2) using codoncode aligner v3.0.2 (CC Cooperation).…”
Section: Methodsmentioning
confidence: 99%
“…The Journal of Animal Genetics (2017) 45, 49-58 and they are not the same subspecies at least in their maternal origins, and the extant wild camel is a separate lineage but not the direct progenitor of the domestic Bactrian camel (Ji et al 2009;Silbermayr et al 2010). In addition, mtDNA sequence analysis of ancient DNA proved to be crucial in resolving domestication processes in dromedaries (Almathen et al 2016).…”
Section: Figure 1 Classification Of the Camelidae Familymentioning
confidence: 99%